Determinant Factors That Influence Repurchase Intention In Patients Of Bhayangkara Tk Ii Mas Kadiran Medan Hospital - Iis Putri Julia; Nur Aisyah; Ahmad Rafiki (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2024)
This study aims to find out what factors influence repurchase intention in patients at Bhayangkara TK II Mas Kadiran Hospital, Medan. This research method uses quantitative methods with associative research types. The sampling technique in this research used simple purposive sampling. The population in this study was 25,625 patients at Bhayangkara TK II Mas Kadiran Hospital, Medan and using the Slovin formula technique with a significance level of 0.05, the total sample in this study was 394 respondents taken from part of the population. The data analysis used in this research is structural equation modeling-partial least squares (SEM-PLS) using SmartPLS software. Based on the results of hypothesis testing, the variables brand association, brand loyalty, customer experience and perceived quality have a positive and significant effect on repurchase intention through customer satisfaction at Bhayangkara TK II Mas Kadiran Hospital, Medan.